Legal Uncertainty Regarding Pretrial Decisions Regarding Objects of Suspect Determination that have been Revoked and Declared Invalid: Ketidak Pastian Hukum Putusan Praperadilan tentang Objek Penetapan Tersangka yang telah Dibatalkan dan Dinyatakan Tidak Sah - Ahmad, Suparji; Wirakusumah, R Ardi (Dame Journal of Law, 2026)
This study examines the phenomenon of repetition of suspect determination in the Indonesian criminal law system, especially after the revocation of suspect determination through the pretrial mechanism. The pretrial process aims to test the legality of the actions of law enforcement officials, such as arrests, detentions, and determination of suspects, in order to protect human rights. However, legal problems arise when investigators again designate a person as a suspect after the determination of the suspect in the case is invalid based on a pretrial verdict, which raises questions about the legality of the act and the potential violation of the principle ne bis in idem, which is the prohibition of prosecuting someone for the same case more than once. This study aims to analyze the authority of investigators in issuing the same investigation warrant after the revocation of the suspect's designation, as well as its impact on the rights of suspects and applicable legal principles, such as justice and legal certainty. Through a normative juridical approach, this study identifies legal loopholes in the regulations governing the repetition of the determination of suspects after the cancellation of pretrial detention. This study also examines the application of the principle ne bis in idem comparatively in international law and Indonesian law, as well as evaluates the supervisory mechanism for investigator authority. The results of the study show that the Indonesian legal system needs significant revisions to provide legal certainty related to the repetition of the determination of suspects and strengthen supervision of law enforcement officials. The study provides recommendations to improve regulations, increase transparency in the legal process, and propose training for law enforcement officials to ensure better protection of human rights in every pro justicia legal process. Thus, this research contributes to the development of a fairer and more efficient criminal justice system, as well as increasing public trust in the integrity of the Indonesian legal system